The prevalence of hoarseness among health care professionals: time trends and effect of remediation in working conditions in 2007-2018 - Vilén Liisa; Atosuo Janne; Putus Tuula (SPRINGER, 2022)
Purpose The purpose of this study was to investigate time trends in the prevalence of hoarseness among health care professionals in primary health care units (PHC) and in hospitals from 2007 to 2018. Moreover, purpose was to discover potential indoor environmental quality (IEQ) risk factors as well as to determine the effect of the remediation of the indoor air problems on the prevalence of hoarseness.
Methods The health status was collected from all employees in these units/hospitals (N = 1564/1199) with questionnaires and the follow-ups were carried out as an open cohort. Based on building condition inspections, buildings were classified to be an "exposed" or "reference" buildings by third-party experts. The before and after remediation results were compared to reference buildings.
Results During follow-up, hoarseness has not increased in those PHC units with good IEQ. In the pilot study, the prevalence of hoarseness in non-exposed reference building was 5.9%, and it stayed approximately at the same level throughout the follow-up. Whereas in buildings with an IEQ problem the prevalence of hoarseness varied between 16.2 and 36.1% and it decreased to 11.4% after the remediations. In a large hospital with severe IEQ problems, the prevalence of hoarseness was 39.1%, and in hospital buildings with a milder exposure 23.3%. The most important risk factors for hoarseness were asthma, allergic rhinitis and IEQ problems.
Conclusion A good indoor environment and the remediation of damaged buildings seem to promote a better condition of the voice in health care workers.